HUBUNGAN ANTARA HIPONIM DENGAN ENTAILMENT DALAM BAHASA JEPANG - Eva Amalijah (Universitas 17 Agustus 1945 Surabaya, 2014)
This articles aims to observe the relationship between hyponym and entailment in Japanese.Semantics is study of language meaning. It is as confirmed by Chomsky (1965), that â€œSemantics is one component of the grammar (the other two components are syntax and phonology) and meaning of a sentence isdetermined by the semantic componentâ€. From the description on hyponim and entailment, it is understoodthat the relationship between hyponym and entailment conveys a sentence parallel meaning. Because of the meaning contained in hiponim also present in entailment. Example: a) I keep a cat //Watashi wa neko okatte imasub) I maintain an animal / /Watashi Doubutsuwa o Katte imasu. In the above example sentence: The catis the hyponym of animaland the truth of the secondsentence (b) is in line with the truth of the first sentence (a) The first sentence means (a) has an absoluterelationship with the second sentence (b). The statement is called the entailment